A Constituição de Identidades, Representações e Violência de Gênero nas letras de RAP(São Paulo na década de 1990) - Carvalho, João Batista Soares de (2006)
The intention with this research was to analyze the representations of sort in the letters of RAP of the Racionais MC's, to understand as the social construction of the manhood and the womanhood happened in this musical expression produced and consumed by parecI of the young of the periphery - SãoPauloCity- duringthe decadeof 1990. It was looked to demonstrate that, while the ethnic representations, religious, of social classes and of the urban violence of the songs found references in the daily one of the young rap's producers, the representation of sort was based mainly in the social opinions preconceived that, nor always, could have been observed in the daily one characterized for the songs. If the masculines integrant of the movement had developed denouncers rhyme and critical in relation to the etnia questions and classes, soon the feminine integrant will go to question, by means of its rhymes, the diseases who affected the lives of millions of poor women and its families. The representations of sort in rap from the feminine insertion in this universe had contributed to perceive as the conceptions of private spaces were crystallized, positions previously detennined for men and women in the singing and in the making of rappers